مؤتمر الصومام عام 1956 وإشكالية تجسيد قراراته - يعيش, محمد (جامعة الوادي - University of Eloued, 2017)
في هذا المقال حاولنا تناول إشكالية مهمة في تاريخ ثورتنا، تمثلت في مسألة تجسيد قرارات مؤتمر الصومام، والتي لم تكن سهلة وممكنة إلا بعد جهد كبير وفترة زمنية، وذلك يرجع إلى عدم انسجام بعض تلك القرارات مع واقع الثورة المعاش، ومثالية بعضها الآخر، وخاصة القرار المتعلق بأولوية الداخل على الخارج وأولوية السياسي على العسكري، وعليه أثيرت معارضة شديدة في الداخل والخارج، وكل ذلك اندرج في إطار الصراع السياسي بين عبان رمضان في الداخل وابن بلة في الخارج، وكانت ساحته الرئيسية قاعدة تونس والأوراس، وتعرضت الثورة لمحنة شديدة، لم تنته إلا بخسائر جسيمة وبجهود ضيعت في حمل المعارضين على تقبل تلك القرارات، وفي نهاية المطاف تبين أن قرارات الصومام وعلى الرغم من بعض الانتقادات كانت مفيدة للثورة على الصعيد التنظيمي والوحدوي، وهذا ما نحاول تناوله في هذا المقال. In this article we have tried to address the problem of the task in the history of our revolution, was the question of the embodiment decisions soummam conference, which were not easy and possible only after considerable effort and time period, due to the incompatibility of some of those decisions with the reality of the revolution pension, and perfect each other, in particular resolution on the primacy of the inside to the outside political priority on the military, and the strong opposition it raised at home and abroad, all of which is integrated as part of a political conflict between Abane at home and the son of injury abroad, and was acquitted Home Tunisia and Aures base, came the revolution severe distress, did not end until a loss and serious efforts wasted in getting opponents to accept those decisions, and ultimately show that the decisions Alsomam despite some of the criticisms have been useful to the revolution on the organizational and Unionist level, and this is what we are trying to be addressed in this article.
مقال
Keywords: الثورة الجزائرية، مؤتمر الصومام، تجسيد قرارات الصومام، معارضة قرارات الصومام